2018
DOI: 10.3390/rs10050804
|View full text |Cite
|
Sign up to set email alerts
|

Performance Assessment of the COMET Cloud Fractional Cover Climatology across Meteosat Generations

Abstract: Abstract:The CM SAF Cloud Fractional Cover dataset from Meteosat First and Second Generation (COMET, https://doi.org/10.5676/EUM_SAF_CM/CFC_METEOSAT/V001) covering 1991-2015 has been recently released by the EUMETSAT Satellite Application Facility for Climate Monitoring (CM SAF). COMET is derived from the MVIRI and SEVIRI imagers aboard geostationary Meteosat satellites and features a Cloud Fractional Cover (CFC) climatology in high temporal (1 h) and spatial (0.05 • × 0.05 • ) resolution. The CM SAF long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…First, Govaerts et al, (2018) [22] demonstrated the improved identification of deep convective clouds by using the recalibrated IR radiances. Second, Bojanowski et al, (2018) [23] and Stockli et al, (2019) [24] used the recalibrated radiances for deriving cloud fractional cover climatology. Finally, Duguay-Tetzlaf et al, (2017) [25] demonstrated the impact of reduced bias and better temporal stability of the recalibrated radiances on their land surface temperature data record.…”
Section: Validationmentioning
confidence: 99%
“…First, Govaerts et al, (2018) [22] demonstrated the improved identification of deep convective clouds by using the recalibrated IR radiances. Second, Bojanowski et al, (2018) [23] and Stockli et al, (2019) [24] used the recalibrated radiances for deriving cloud fractional cover climatology. Finally, Duguay-Tetzlaf et al, (2017) [25] demonstrated the impact of reduced bias and better temporal stability of the recalibrated radiances on their land surface temperature data record.…”
Section: Validationmentioning
confidence: 99%
“…This value lies between the GCOS-defined stability requirements for thick and thin clouds. This negative trend is related to the overestimation of CFC before 1996 and to a statistically-detectable break in 1996 (standard normal homogeneity test T(k) > 10.02 for a 95% confidence level [30,49]). When comparing to three long CDRs from polar-orbiting AVHRR sensors, COMET was most similar to PATMOS-x [50].…”
Section: Resultsmentioning
confidence: 98%
“…All results and reference SYNOP datasets shown here were described in depth within the dataset validation report [29] and were discussed in [30]. COMET bias (trueness) was measured by the Mean Bias Error (MBE) metric, and precision was measured by the bcRMSE metric.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations